Digital Transformation of Whistleblower Legal Protection in Eradicating Corruption in Indonesia - Fahririn Fahririn; Ani Siska MY; Nut Nut (CV. Era Digital Nusantara, 2025)
Digital transformation has transformed the Indonesian corruption eradication landscape, creating a paradox where technology facilitates new modes of corruption while providing innovative solutions for detection and prevention. Research purpose: the challenges of legal protection for whistleblowers in the digital era, particularly the unpreparedness of conventional systems to face cyber threats. The research method uses a normative legal approach with a statutory approach and a case approach, analyzing regulations related to whistleblower protection and empirical cases such as Eko Sulistyo, who experienced a massive digital attack. Data sourced from primary, secondary, and tertiary legal materials were analyzed descriptively, comparatively, prescriptively, and through gap analysis. The discussion reveals that although the Corruption Eradication Commission (KPK) has developed the JAGA and GOL digital platforms, the Indonesian legal framework still has fundamental weaknesses: the absence of conflict of interest regulations, a weak data security system, the absence of post-protection phase regulations, limited economic protection, and the absence of a unified database. The study concludes that the digital transformation of whistleblower protection requires a holistic approach that integrates technological, legal, and social aspects, including regulatory reformulation to accommodate digital threats, the development of robust cybersecurity infrastructure, and the development of a comprehensive and sustainable protection system.